Development of The Cibeet River Natural Tourism In Cijeruk Village Cilacap Regency - Saputra, Jumadil; Lugiana, Yuda; Robiatul A, Wahda; Nazila, Siti Desi; Noor F, Deng Dewi; Septiani, Lisma; Fauziah, Irma Silvia; Assidqi, Hasbi; Maulana, Deni; Sopia, Dea; Wahyuni, Arni Sri; Nurhayati, Ai; Pratiwi, Anggia Suci; Hendrawan, Budi; Mujiarto, Mujiarto (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Indonesia is a country that has abundant natural resources. We can manage natural resources to take advantage of it, for example, as a place for tourism, for example natural tourism. The implementation of this community service activity was carried out in Cijeruk Village, Kujang Hamlet, Sawah Tengah. The community service will be held on 10 August – 12 September 2021. The target of this community service is the natural resources in Cijeruk Village which have the potential to be used as a tourist spot. The purpose of this community service is to help develop Cijeruk Village and improve the economy of the people there through the construction of tourist attractions. This community service method is in the form of involving village officials, the community, and local youth organizations to be involved in the development of the Cibeet River nature tourism. The implementation carried out is revamping the Cibeet River area, making and mapping photo spots, making chairs, making access roads and others. The result of the development of the Cibeet River natural tourism is the development of the Cibeet River natural tourism, which is used as a rest area and a place to play. In conclusion, the existence of Kali Cibeet natural tourism can help the development of Cijeruk Village, which is marked by the large number of people who come to the Kali Cibeet Nature tourism and the community's economy can increase by adding new livelihoods for the community such as building stalls in tourist areas, parking lots, rental places mats, hammocks etc.